Heavy metal pollution and health risk assessment of agricultural soils in a typical peri-urban area in southeast China. (1st February 2018) - Huang, Ying; Chen, Qianqian; Deng, Meihua; Japenga, Jan; Li, Tingqiang; Yang, Xiaoe; He, Zhenli
Abstract: Heavy metal pollution in peri-urban areas in China is serious and complex. We thus developed an integrated evaluation method to assess heavy metal pollution and potential health risk to residents in a typical peri-urban area with diverse anthropogenic emission sources and cropping systems. Ecological risk was evaluated using Nemerow's synthetical pollution index ( P n ) and Potential ecological risk index (RI). Then polluted areas and responsible emission sources were identified by GIS mapping. Health risk caused by food intake and soil exposure was calculated by accounting for the influence of anthropogenic emissions and cropping systems. Agricultural soils in the study area were polluted by cadmium (Cd), mercury (Hg), lead (Pb), and arsenic (As). High concentrations mainly occurred near the mining area and along the roadsides. The accumulation of heavy metals in crops followed the order of tea leaves > rice grain > vegetables. The hazard index of potential human health risk caused by chronic soil exposure and food intake was 15.3, indicating obvious adverse health effects. 87.5% of health risk was attributed to food consumption, and significantly varied among different cropping systems with the decreasing order of rice (10.44) >vegetable (2.86) > tea (0.05). The integrated method of ecological and health risk index, which takes consideration of both anthropogenic emission and cropping system can provide a practical tool for evaluating of agricultural soil in the peri-urban area regrading different risk factors. Graphical abstract: Highlights: Heavy metal influenced by different anthropogenic emissions and cropping systems were compared. The major pollutants were As, Cd, Pb, which mainly derived from mining and traffic emissions. Health hazard index of rice intake (10.44) was bigger than vegetable (2.86) and tea (0.05). Health risk provided better evaluation for heavy metal pollution in peri-urban area.